AUDIENCE PERCEPTION OF THE USE OF TELEVISION JINGLES IN CREATING AWARENESS OF E-PAYMENT SYSTEM - Jemimah Deynum Elisha; Ayodele Babatunde Joseph (International Studies Journal)
The sole purpose of the media is to share information on current affairs, news and entertainment. In this era of digitization, sharing, promoting and usage of Digital Payment System in the open marketplace is essential for the audience. The main objective of promoting the electronic payment system is to create awareness among the people especially and ensure they are conscious of the advantages of digital payment services and understand the importance of converting the country into a cashless economy. The audience perception of the use of television jingles in creating awareness of e-payment system can be a mixed bag. On one hand, television jingles have the potential to create catchy and memorable tunes that can stick in people’s minds, effectively promoting e-payment systems and increasing their visibility. On the other hand, there are several critical aspects to consider when evaluating the effectiveness of television jingles in shaping audience perception. The paper, examine the conceptional clarifications on perception, television jingles and electronic payment system also the impact of television jingles on audience perception. The study was anchored on consistency theory. It also outlines the challenges of television jingles, how it has limited span to convey information which can make it challenging to provide comprehensive information amongst others.